Optimization API for customer acquisition - Bihány, Daniel; Umlauf, Miroslav; Novotný, Ota, 1971-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The subject of this master’s thesis is the development of an analytics service for a corporate client of a consulting firm. The service is aimed at improving the customer acquisition rate of the client’s B2B business. The thesis focuses on the development of several components of the service, particularly its web API and database server, as well as the data-processing pipelines necessary to meet the client’s requirements. The service is hosted on Microsoft Azure. The primary objective of the thesis is to develop and integrate the components of the service, such that the client can begin its utilization. The thesis begins by describing the business problem and requirements, followed by an introductory overview of the service and the processes related to its usage. Next, the implementation of the service is outlined in detail. Finally, the developed solution is evaluated, with respect to the client’s feedback and usage.
Vedoucí práce: Miroslav Umlauf
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses